A rare case of varicella zoster virus encephalitis in a 16 years old unvaccinated girl - Abdul Wali Khan; Abad Khan; Muhammad Ishaq; Irfan Ullah; Marhami Fahriani (Trends in Infection and Global Health, 2021)
We reported a 16-year-old girl, with diffuse vesicular rashes all over the body, presented to the emergency department with altered mental status, irritability, persistent fever and one episode of a generalized tonic-clonic seizure. After thorough evaluation and investigations, the case was a varicella zoster-associated encephalitis in an unvaccinated patient. Appropriate treatment was initiated, the patient was then shifted to the critical care and subsequently discharged with no sequelae. Early diagnosis and treatment should be emphasized as they play an important role in the clinical outcome of chickenpox-associated encephalitis.